2002
DOI: 10.1002/app.11140
|View full text |Cite
|
Sign up to set email alerts
|

Impact resistance of fibrous glass reinforced plastics using polycarbonate‐polydimethylsiloxane block copolymer

Abstract: By using reactive polydimethylsiloxanes that have phenolic hydroxyl groups at the ends of the chain, a polycarbonate-polydimethylsiloxane (PC-PDMS) block copolymer was prepared, and the properties of fibrous glass reinforced plastics (GF-PC) using this copolymer were examined. The Izod impact value of the PC-PDMS/GF composite increases with an increase in the degree of polymerization of reactive PDMS (n) between 40 and 160. When n is 40, the Izod impact value of the PC-PDMS/GF composite is equal to that of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…PC–PDMS block copolymers used in this study were the same as prepared in a previous article 14, 16, 17. Table I lists the characteristics of the resulting PC–PDMS block copolymers.…”
Section: Methodsmentioning
confidence: 99%
“…PC–PDMS block copolymers used in this study were the same as prepared in a previous article 14, 16, 17. Table I lists the characteristics of the resulting PC–PDMS block copolymers.…”
Section: Methodsmentioning
confidence: 99%
“…Beach et al showed that the incorporation of 25 weight percent PDMS blocks into PC reduced the ductile brittle transition temperature from −20°C to −110°C. In addition, Okamoto showed that glass‐filled composites based a PC‐PDMS multiblock copolymer matrix can provide higher impact strength and lower melt viscosity than glass‐filled PC. Further, Nodera and Kanai showed that the incorporation of PDMS into PC via block copolymerization enhances flame retardancy even at PDMS contents as low as 1.0 wt%.…”
Section: Introductionmentioning
confidence: 99%
“…He has adopted the firstorder shear deformation theory and tensor polynomial failure criteria. Okamoto has investigated the impact resistance of glass fiber reinforced PC using polydimethylsiloxane (PDMS) block copolymer [10]. Very recently, the hydrolytic stability of PC/GF composites has been reported by Jancar [11].…”
Section: Introductionmentioning
confidence: 99%